XV WORLD FORESTRY CONGRESS - Building a Green, Healthy and Resilient Future with Forests - 2–6 May 2022 | Coex, Seoul, Republic of Korea - Trébuchon, JF (BOIS & FORETS DES TROPIQUES, 2022)
SIDE EVENTS Side events provide an opportunity for sharing expertise, best practices and innovations as well as for increasing opportunities for dialogue and exchange amongst the Congress’ participants on the theme and subthemes of the Congress. These events are open to all interested participants who are registered for the Congress. Organizers of confirmed events are invited to upload their event flyers through the online submission platform no later than 15 February 2022. Side events currently confirmed The final list of confirmed events will be posted shortly on the Congress website. Building data foundations for sustainable forest management: integration, collaboration and experience in reporting at global and regional scales to show progress towards green, healthy and resilient forest. Contact: Stefanie Linser, Email: stefanie.linser@efi.int Criteria and Indicators to strengthen sustainable forest management in the Caucasus and Central Asia. Contact: Stefanie Linser, Email: stefanie.linser@efi.int NEW DATE! New opportunities for Teak sector in the post-COVID-19 Scenario - TEAKNET. Contact: P. K. Thulasidas, Email: pktdas@gmail.com Services and logistic information: logistics@wfc2021korea.org General inquiries: WFC-2021-Events@fao.org.